A Bibliometric Review of Remote Working - DIFITRI, ENZILYNA (Trunojoyo University of Madura, 2025)
The awareness that workers can still work from home during pandemi covid 19 has given rise to the idea of developing remote working methods. Remote working has become a very interesting topic to research. Remote working method, as it can offer both benefits and challenges. Research trends that have been published on the topic of remote working ing in the 2000-2025 periods. The method used in this study was to identify the number of journals using Harzing's Publish or Perish software, as well as bibliometric analysis using VOSviewer. The results showed that there were 999 publications with 17888 citations and 3577 cites/year that discussed remote working. There are seven main clusters based on the results of bibliometric analysis. This article also provides information related to research topics that have not been widely carried out so that it can provide benefits for stakeholders who may need it for further research..